Development of a food safety education program on CD/ROM for 4th, 5th, and 6th grade children - Bryant, Toni Jo (Kansas State University, 2004)
This research created an interactive, multimedia, food safety education program on CD/ROM for fourth through sixth grade school children. The project was divided into three stages: 1) a survey to assess children's needs, 2) program development, and 3) Beta-testing the program with content experts and the targeted audience. A needs assessment survey was administered to children, 9 to 12 years of age, who were members of a 4-H, Boys and Girls Clubs, or after school program. The survey collected demographic data, food handling frequencies/practices, handwashing habits, and computer usage/media preferences. Children were found to be active in food handling/preparation and stated they knew the definition of food safety. Many, however, were unsure of the meaning of cross-contamination, how to use a thermometer, and were inconsistent with safe handwashing practices. Almost 92% of respondents reported using the computer daily, weekly, or monthly and 91% liked using the computer for learning. To facilitate design of the food safety education program, current food safety education programs were reviewed. At the time, there were limited numbers of programs directed at children and even fewer computer-based. A multimedia specialist assisted in the creation of the food safety education program on CD/ROM titled, "Kid Chef and the Clean Kitchen Crew." The program was divided into four chapters: 1) food safety and foodborne illness, 2) handwashing importance and handwashing techniques, 3) foodborne pathogens, and 4) food safety practices from purchase to cooking to serving. Interactive and multimedia components were used throughout the program. Beta-testing with experts from food safety, multimedia, education, extension, and technology ensured that the program was factual and appropriate for fourth through sixth grade students. Additional Beta-testing with ten children in the targeted age group illustrated acceptance, ease of understanding, and navigation. Changes were made prior to each subsequent critique. The reviewers and target audience indicated the CD format was acceptable for presenting food safety education. Recommendations included increasing the amount of animation, video clips, questions, and translation into Spanish. It is further suggested that the program be tested for effectiveness via a pre/post test design.
Keywords: Food handling; Food safety and children; Consumer food safety; Handwashing; Children and cooking; Education, Health (0680)